Scalable Flexible Perovskite Solar Cells Based on a Crystalline and Printable Template with Intelligent Temperature Sensitivity. Issue 4 (27th January 2022) - Yang, Xia; Yang, Hanjun; Su, Meng; Zhao, Jianming; Meng, Xiangchuan; Hu, Xiaotian; Xue, Tangyue; Huang, Zengqi; Lu, Ying; Li, Yuzhan; Yang, Zhou
Abstract : The control of crystallization and printability of large‐area perovskite layers is crucial to facilitating their commercial development in flexible electronics. Considering the benefits of the liquid crystals with intelligent temperature sensitivity for the printable and crystalline template of a scalable perovskite film, a liquid crystal 4((6(acryloyloxy)hexyl)oxy)benzoic acid (6OBA) is introduced. The 6OBA shows a liquid crystal temperature range matching with the thermal annealing temperature of perovskite films. A desire printability of perovskite inks for scalable and homogeneous devices is guaranteed due to the fluidity of the 6OBA additive at room temperature. Moreover, the crystalline 6OBA promotes crystallization of perovskite films during the thermal annealing process, which can also release the residual stress of the whole layer. The optimized perovskite solar cells (PSCs) with 6OBA exhibit superior power conversion efficiency values of 19.87% for flexible devices (1.01 cm 2 ) and 14.74% for flexible modules (25 cm 2 ). The unencapsulated devices can maintain >90% of their original efficiency after 1500 h in the ambient atmosphere. Furthermore, the flexible PSCs exhibit outstanding bending resistance, retaining over 88% of their initial efficiency after 1000 bending cycles at a radius of 3 mm. This work provides a facile strategy for accelerating the development of flexible electronics. Abstract : Liquid crystal 4((6(acryloyloxy)hexyl)oxy)benzoic acid (6OBA) is introduced as an intelligent temperature‐sensitive template to simultaneously enhance the large‐scale printability of perovskite inks and the quality of perovskite film for improving the efficiency and mechanical stability of perovskite solar cells (PSCs). The optimized PSCs with 6OBA exhibit superior efficiency of 19.87% for flexible devices (1.01 cm 2 ) and 14.74% for flexible modules (25 cm 2 ).